Molecular Characterization of a Rigid Rod-Shaped Virus Isolated from Frangipani (Plumeria sp.) Showing Mosaic Symptom in Taiwan - Choliq, Fery Abdul; Chen, Tsang Hai; Sulistyowati, Liliek (University of Brawijaya, 2012)
Abstract Frangipani is an important succulent plant around the worlds and also in Taiwan, for example, Plumeria rubra is widely grown as a popular ornamental tree in parks and landscaped establishments in Taiwan. Recently, a new disease in frangipani with mosaic and distortion symptoms was found in Taiwan. No viruses caused frangipani disease has been reported in Taiwan and the references about frangipani disease are still limited and only Frangipani mosaic virus (FrMV) was found. In this study, the molecular properties of a virus isolated from symptomatic frangipani in south Taiwan, such as Pingtung, Kauhsiung and Tainan were investigated. The virus with rod-shaped particles of 300 nm long and 18 nm in diameter was examined inside diseased leaves by electron microscopy. The purified virus particles showed the typical UV spectrum of tobamoviruses with A260/A280 value of 1.29 and maximum and minimum absorption at 260 nm and 249 nm, respectively. The molecular weight of19.5 kDa as the size of coat protein of tobamoviruses was estimated bysodium dedocyl sulfate-polyacrylamide gel (SDS-PAGE). Furthermore, the degenerate primers for tobamoviruses were used to amplify 568 bp and 400 bp of the DNA fragments in RT-PCR and nested PCR, respectively. Based on these results, it was confirmed that the rigidrod-shaped virus isolated from mosaic symptom of frangipani leaves is an isolate of FrMV, belonging to the genus Tobamovirus. This is the first report thatFrMV infecting Plumeria sp.in Taiwan. Keywords: Frangipani plant, mosaic disease, FrMV, Tobamovirus